Relationships of Chemical Elements and their Environmental Impacts in Groundwater, Soil, and Fodder Plants in Arid Land - Hamdan, Ali; Khozyem, Hassan; Elbadry, Eman (Economic and Environmental Geology, 2021)
The relationship of both heavy metals and major elements in soil, plants, and groundwater was studied in a hyper-arid area and depends completely on the groundwater to cover its all needs. The study reviles that 27.3% of the studied groundwater was strongly acidic and has very low pH values (<pH 5.5). The groundwater has a serious corrosion effect on the metallic infrastructure, a negative effect on the plant growth rate, and an increase in soil degradation and acidity. The distribution of both heavy metals (Cd, Ni, Fe, Mn, Pb, and Zn) and major elements (Ca, Mg, Na, and K) in groundwater, soil, and Alfalfa plants are identical. The high concentration of elements in groundwater impacted both plants and soil. In general, not all the studied groundwater is suitable for irrigation or day-life uses; therefore, a pre-use treatment is necessary for most of the studied sites. KCI Citation Count: 0